MYOCARDIUM OF NEWBORNS AND METHODS OF CORRECTION OF ITS POSTHYPOXIC PATHOLOGY - V.P. Bulatov; L.K. Fazleeva; M.N. Alieva; L.I. Sattarova; A.P. Solonenko ("Paediatrician" Publishers LLC, 2008)
Biochemical analysis of children's blood with posthypoxic myocardial ischemia shows increase of creatine phosphokinase (CPK), lactate dehydrogenase (LDH) and troponin. The search of optimal methods of correction posthypoxic myocardial pathology is lasts. Authors examined 104 newborns of first day of living. 83 children had perinatal hypoxia and were observed in children republic clinical hospital of ministry of public health of Tatarstan republic. 62 patients received classical therapy (group 1), and the rest of children received treatment with dimephosphon (group 2). Control group 3 consists of 21 relatively healthy newborns. The activity of LDH, CPK and Troponin (TNI) was registered in all children. Besides, a registration of electrocardiogram (ECG) as provided. destabilization of electrical activity of myocardium and increase of cardio tropic enzymes activity and blood concentration of TNI was estimated as consequences of hypoxia. The level of TNI had a tendency to increasing in children, the state of who was severe at the time of admission. The results of study demonstrate significantly higher therapeutic effect on the assumption of addition of dimephosphon to the standard course of treatment. Key words: newborns, hypoxia, troponin I, creatine phos phokinase, lactate dehydrogenase, electrocardiography.